On the Role of the Governmental Agreement in Breaking Political Deadlocks - Robert A.J. Dur; Otto H. Swank (Tinbergen Institute, 1997)
Resistance to socially desired reforms may arise from uncertainty about the consequences of reforms at the individual level (Fernandez and Rodrik, 1991). Without a binding commitment, a promise to compensate losers will not raise support for reforms due to a credibility problem. This paper shows that voting simultaneously on several reforms may solve the credibility problem. It is argued that the governmental agreement in the Netherlands has served as a means to vote simultaneously on several reforms and has helped breaking political deadlocks. Moreover, our model provides an explanation for some perceived changes in the Dutch policy making process.
Keywords: 330